2018
DOI: 10.3389/fcimb.2017.00521
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Amblyomma variegatum Saliva on Bovine Cells: Characterization of Cellular Responses and Identification of Molecular Determinants

Abstract: The tropical bont tick, Amblyomma variegatum, is a tick species of veterinary importance and is considered as one of major pest of ruminants in Africa and in the Caribbean. It causes direct skin lesions, transmits heartwater, and reactivates bovine dermatophilosis. Tick saliva is reported to affect overall host responses through immunomodulatory and anti-inflammatory molecules, among other bioactive molecules. The general objective of this study was to better understand the role of saliva in interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 87 publications
2
6
0
Order By: Relevance
“…These factors have been reported to play a role in the activation and/or recruitment of multiple resident and infiltrating cell types at the tick bite site, including macrophages, mast cells, dendritic cells, endothelial cells, keratinocytes, and lymphocytes, as well as in the polarization of an initial Th1 helper response towards a Th2 orientation, considered to be more favourable to tick blood-feeding [29]. Here we showed that IrSPI inhibits mitogen-induced proliferation of murine CD4 + T cells, as has been reported for saliva of not only I. ricinus [48], but also several other tick species including D. andersoni [49], A. variegatum [50], and I. dammini [51]. It is noteworthy that in our study, IrSPI inhibited secretion of IL-9, which promotes the proliferation of CD4 + rather than CD8 + T cells [52].…”
Section: Discussionsupporting
confidence: 83%
“…These factors have been reported to play a role in the activation and/or recruitment of multiple resident and infiltrating cell types at the tick bite site, including macrophages, mast cells, dendritic cells, endothelial cells, keratinocytes, and lymphocytes, as well as in the polarization of an initial Th1 helper response towards a Th2 orientation, considered to be more favourable to tick blood-feeding [29]. Here we showed that IrSPI inhibits mitogen-induced proliferation of murine CD4 + T cells, as has been reported for saliva of not only I. ricinus [48], but also several other tick species including D. andersoni [49], A. variegatum [50], and I. dammini [51]. It is noteworthy that in our study, IrSPI inhibited secretion of IL-9, which promotes the proliferation of CD4 + rather than CD8 + T cells [52].…”
Section: Discussionsupporting
confidence: 83%
“…These factors have been reported to play a role in the activation and/or recruitment of multiple resident and infiltrating cell types at the tick bite site, including macrophages, mast cells, dendritic cells, endothelial cells, keratinocytes, and lymphocytes, as well as in the polarisation of an initial Th1 helper response towards a Th2 orientation, considered to be more favourable to tick blood feeding [11]. Here we showed that IrSPI inhibits mitogen-induced proliferation of murine CD4 + T cells, as has been reported for saliva of not only I. ricinus [29], but also several other tick species including D. andersoni [30], A. variegatum [31], and I. dammini [32]. It is noteworthy that in our study, IrSPI inhibited secretion of IL-9, which promotes the proliferation of CD4 + rather than CD8 + T cells [33].…”
Section: Discussionsupporting
confidence: 80%
“…These genes are highly polymorphic and are less defined in species such as cattle. Several tick immunological studies have demonstrated that different MHC2 classes are responsible for tick resistance or susceptibility [ 115 , 116 ]; however, these findings have not been used to inform vaccine research directly. Some researchers have tried to predict B cell and/or T cell binding epitopes in putative tick vaccine candidates (reviewed by Lew-Tabor and Rodriguez Valle [ 6 , 117 ]); however, the tools for these bioinformatics predictions for use in non-human hosts have yet to be developed.…”
Section: Potential Constraints Toward Cocktail Vaccine Efficacymentioning
confidence: 99%